Plant sterol ester diet supplementation increases serum plant sterols and markers of cholesterol synthesis, but has no effect on total cholesterol levels. Issue 169 (May 2017) - Weingärtner, Oliver; Bogeski, Ivan; Kummerow, Carsten; Schirmer, Stephan H.; Husche, Constanze; Vanmierlo, Tim; Wagenpfeil, Gudrun; Hoth, Markus; Böhm, Michael; Lütjohann, Dieter; Laufs, Ulrich
Highlights: Plant sterol ester supplemented margarine increases plant sterol serum levels. Plant sterol ester supplemented margarine increases serum levels of markers of cholesterol synthesis. Plant sterol ester supplemented margarine has no effect total serum cholesterol levels, ROS and monocyte activation. Abstract: This double-blind, randomized, placebo-controlled, cross-over intervention-study was conducted in healthy volunteers to evaluate the effects of plant sterol ester supplemented margarine on cholesterol, non-cholesterol sterols and oxidative stress in serum and monocytes. Sixteen volunteers, average age 34 years, with no or mild hypercholesterolemia were subjected to a 4 week period of daily intake of 3 g plant sterols per day supplied via a supplemented margarine on top of regular eating habits. After a wash-out period of one week, volunteers switched groups. Compared to placebo, a diet supplementation with plant sterols increased serum levels of plant sterols such as campesterol (+0.16 ± 0.19 mg/dL, p = 0.005) and sitosterol (+0.27 ± 0.18 mg/dL, p < 0.001) and increased markers of cholesterol synthesis such as desmosterol (+0.05 ± 0.07 mg/dL, p = 0.006) as well as lathosterol (+0.11 ± 0.16 mg/dL, p = 0.012). Cholesterol serum levels, however, were not changed significantly (+18.68 ± 32.6 mg/dL, p = 0.052). These findings could not be verified in isolated circulating monocytes. Moreover, there was no effect on monocyte activation and no differences with regard to redox state after plant sterol supplemented diet. Therefore, in a population of healthy volunteers with no or mild hypercholesterolemia, consumption of plant sterol ester supplemented margarine results in increased concentrations of plant sterols and cholesterol synthesis markers without affecting total cholesterol in the serum, activation of circulating monocytes or redox state.